Psychomotor Behavior: A Practical Approach in Drosophila - Iliadi, Konstantin G.; Gluscencova, Oxana B.; Boulianne, Gabrielle L. (Frontiers in Psychiatry, 2016)
Psychomotor behaviors are governed by fine relationships between physical activity and cognitive functions. Disturbances in psychomotor development and performance are a hallmark of many mental illnesses and often appear as observable and measurable behaviors. Here, we describe a new method called an “equilibrist test,” which can be used to quantify psychomotor learning and performance in Drosophila. We also show how this test can be used to quantify motor disturbances at relatively early stages in the development of neurodegenerative diseases.